Pengembangan Instrumen Penilaian Menggunakan Google Form Pada Pembelajaran Integratif Pendidikan Agama Islam di SMP IT Qurrata A'yun Batusangkar - Yozara Hendri; Susrizal, Silvia; Herawati, Susi; Fadriati; Gustina (Program Studi Pendidikan Agama Islam, 2022)
This research starts from the problems that occur in the field and the current situation, at this time the covid-19 pandemic which requires all work to be done online and what is happening in the field is inversely proportional to the current situation which is at SMP IT Qurrata A'yun Batusangkar still using an offline assessment or evaluation system or still using paper in their cognitive, affective and psychomotor assessments. Then another problem is that the google form as a tool to facilitate evaluation activities is usually only used for cognitive assessment and another problem is that PAI material has never been linked or integrated with other subject matter, what happens is that on the contrary, other existing subject matter is integrated into PAI material. . Therefore, the researcher developed an assessment instrument using the google form in PAI integrative learning at SMP IT Qurrata A'yun Batusangkar. This study aims to produce a valid and practical cognitive, affective and psychomotor assessment instrument using google form in PAI learning at SMP IT Qurrata A'yun Batusangkar. The research used by the author is a type of development research (R&D) with ADDIE. The stages of research using the ADDIE model are Analysis, Design, Development, Implementation, and Evaluation. Based on the validation test and the practicalization of the assessment instrument using the google form in PAI integrative learning, it shows that the assessment instrument is categorized as valid with an index of 0.75 for cognitive, affective and psychomotor. Meanwhile, from a practical point of view, the assessment instrument using the google form is categorized as very practical with an index of 0.85 for cognitive, 0.86 for affective, 0.90 for psychomotor.